The cell cycle- and insulin-signaling-inhibiting miRNA expression pattern of very small embryonic-like stem cells contributes to their quiescent state. (August 2015) - Maj, Magdalena; Schneider, Gabriela; Ratajczak, Janina; Suszynska, Malwina; Kucia, Magda; Ratajczak, Mariusz Z
Murine Oct4 +, very small embryonic-like stem cells (VSELs), are a quiescent stem cell population that requires a supportive co-culture layer to proliferate and/or to differentiate in vitro . Gene expression studies have revealed that the quiescence of these cells is due to changes in expression of parentally imprinted genes, including genes involved in cell cycle regulation and insulin and insulin-like growth factor signaling (IIS). To investigate the role of microRNAs (miRNAs) in VSEL quiescence, we performed miRNA studies in highly purified VSELs and observed a unique miRNA expression pattern in these cells. Specifically, we observed significant differences in the expression of certain miRNA species (relative to a reference cell population), including (i) miRNA-25_1 and miRNA-19 b, whose downregulation has the effect of upregulating cell cycle checkpoint genes and (ii) miRNA-675-3 p and miRNA-675-5 p, miRNA-292-5 p, miRNA-184, and miRNA-125 b, whose upregulation attenuates IIS. These observations are important for understanding the biology of these cells and for developing efficient ex vivo expansion strategies for VSELs isolated from adult tissues.